Pengaruh Finansial Literacy dan Financial Self Efficacy terhadap Perilaku Belanja Online di Kota Makassar: (Studi Kasus Cash on Delivery pada Pengguna Ecommerse Shopee) - Hasmiati Hasmiati; Andi Batary Citta; Sukmatica Slamet (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This research aims to determine the influence of Financial Literacy and Financial Self Efficacy on Online Shopping Behavior in Makassar City (Case Study: Cash On Delivery among Shopee e-commerce users). This research is research that uses quantitative methods. The population in this study were Shopee users who used COD payments more than once. The sample in this study consisted of 100 respondents using the formula Hair et al. Data collection techniques use observation, interviews and questionnaires. The data analysis techniques used in this research are validity and reliability tests, as well as normality tests, multicollinearity tests and heteroscedasticity tests as prerequisites for classical assumption tests. And the data analysis method uses multiple linear regression analysis with the R2 test, t test, and F test. It is then processed using computer equipment via the IBM SPSS version 23.0 program. The results of this research show that financial literacy has an influence on online shopping behavior. Financial self-efficacy has no influence on online shopping behavior. And financial literacy and financial self-efficacy simultaneously or together have a significant effect on online shopping behavior.